PENGARUH ZAKAT DAN INFAQ DALAM PENGENTASAN KEMISKINAN DI INDONESIA PERIODE TAHUN 2015-2021 - Duriatin Koni’ah; Miftakhul Choiri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Poverty in developing countries is a complex issue, although some countries have managed to grow their production and national income. Zakat and Infaq play a key role in the effort to overcome poverty. Zakat is not only a direct aid to the poor in a consumptive manner, but also aims to address the root causes of poverty in a more sustainable way. The purpose of this study is to understand how zakat and infaq contribute to reducing poverty in Indonesia from 2015 to 2021. The research method used is a quantitative approach with multiple linear regression analysis. The data used is secondary data from BAZNAS Indonesia. The research findings show that zakat and infaq have a significant effect on reducing poverty levels in Indonesia. Individually, zakat and infaq have a negative influence on poverty, but together, they have a positive influence in overcoming the problem of poverty in Indonesia. Based on testing using multiple regression analysis, the t-test shows that Zakat has a partial effect on poverty alleviation. This is shown from the value 2,822 > 0,0477 then, Infaq also has a partial effect on poverty alleviation seen from the value nilai 2,060 > 0,1083. The F test shows that the variables of Zakat and Infaq have a simultaneous effect on poverty alleviation 9,796 > 0,0287.